Alternating series 3

Calculus Level pending

Let ( x 1 ) (|x| \leq 1) and ( 0 < a 1 ) (0 < a \leq 1) .

Let g ( x ) = n = 3 x n 2 ( n 2 ) ( n 1 ) n g(x) = \sum_{n = 3}^{\infty} \dfrac{x^{n - 2}}{(n - 2)(n - 1)n} and f ( x ) = n = 3 ( 1 ) n + 1 x n 2 ( n 2 ) ( n 1 ) n f(x) = \sum_{n = 3}^{\infty} (-1)^{n + 1} \dfrac{x^{n - 2}}{(n - 2)(n - 1)n} .

(1): Show d d x ( f ( x ) ) x = a = d d x ( g ( x ) ) x = a \dfrac{d}{dx}(f(x))|_{x = a} = \dfrac{d}{dx}(g(x))|_{x = -a} .

(2): If A C \overleftrightarrow{AC} is tangent to f ( x ) f(x) at A : ( 1 , f ( 1 ) ) A: (1,f(1)) and B D \overleftrightarrow{BD} is tangent to g ( x ) g(x) at B : ( 1 , g ( 1 ) ) B: (-1,g(-1)) , find the tangent lines to both curves and find the distance B C \overline{BC} to 6 decimal places.

Refer to previous problem

Bonus:

Let j j be a positive odd integer and ( 0 < a 1 ) (0 < a \leq 1) and x 1 |x| \leq 1 .

If g ( x ) = n = j + 2 x n j 1 ( n j 1 ) ( n j ) ( n ) g(x) = \sum_{n = j + 2}^{\infty} \dfrac{x^{n - j - 1}}{(n - j - 1)(n - j) \cdot \cdot \cdot (n)} and f ( x ) = n = j + 2 ( 1 ) n + 1 x n j 1 ( n j 1 ) ( n j ) ( n ) f(x) = \sum_{n = j + 2}^{\infty} (-1)^{n + 1} \dfrac{x^{n - j - 1}}{(n - j - 1)(n - j) \cdot \cdot \cdot (n)} , show f ( a ) = g ( a ) f(a) = -g(-a) and d d x ( f ( x ) ) x = a = d d x ( g ( x ) ) x = a \dfrac{d}{dx}(f(x))|_{x = a} = \dfrac{d}{dx}(g(x))|_{x = -a} .


The answer is 0.044888.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 20, 2018

Note: You can check that both series above converge on [ 1 , 1 ] [-1,1] .

Let h ( x ) = n = 3 x n n d d x ( h ( x ) ) = n = 3 x n 1 = x 2 1 x h(x) = \sum_{n = 3}^{\infty} \dfrac{x^n}{n} \implies \dfrac{d}{dx}(h(x)) = \sum_{n = 3}^{\infty} x^{n - 1} = \dfrac{x^2}{1 - x} .

Let u = 1 x d u d x h ( x ) = 0 x x 2 1 x d x = u = 1 -x \implies du - -dx \implies h(x) = \int_{0}^{x} \dfrac{x^2}{1 - x} dx = 1 1 x ( 1 u + 2 u ) d u = ln ( 1 u ) + 2 u u 2 2 1 1 x = ln ( 1 1 x ) x x 2 2 \int_{1}^{1 - x} (\dfrac{-1}{u} + 2 - u) du = \ln(\dfrac{1}{u}) + 2u - \dfrac{u^2}{2}|_{1}^{1 - x} = \ln(\dfrac{1}{1 - x}) - x - \dfrac{x^2}{2} on x < 1 |x| < 1 .

Let w ( x ) = n = 3 x n 1 ( n 1 ) n d d x ( w ( x ) ) = w(x) = \sum_{n = 3}^{\infty} \dfrac{x^{n - 1}}{(n - 1)n} \implies \dfrac{d}{dx}(w(x)) = n = 3 x n 2 n = 1 x 2 n = 3 x n n = \sum_{n = 3}^{\infty} \dfrac{x^{n - 2}}{n} = \dfrac{1}{x^2}\sum_{n = 3}^{\infty} \dfrac{x^n}{n} = 1 x 2 ( ln ( 1 1 x ) x ) 1 2 \dfrac{1}{x^2}(\ln(\dfrac{1}{1 - x}) - x) - \dfrac{1}{2} \implies w ( x ) = ϵ x 1 x 2 ( ln ( 1 1 x ) x ) 1 2 d x w(x) = \int_{\epsilon}^{x} \dfrac{1}{x^2}(\ln(\dfrac{1}{1 - x}) - x) - \dfrac{1}{2} \:\ dx .

Let I ( x ) = ϵ x 1 x 2 ( ln ( 1 1 x ) x ) d x I(x) = \int_{\epsilon}^{x} \dfrac{1}{x^2}(\ln(\dfrac{1}{1 - x}) - x) dx

Let u = ln ( 1 1 x ) x , d u = x 1 x , d v = x 2 d x u = \ln(\dfrac{1}{1 - x}) - x, du = \dfrac{x}{1 - x}, dv = x^{-2} dx and v = 1 x v = \dfrac{-1}{x}

I ( x ) = 1 x ( ln ( 1 1 x ) x ) ) ϵ x + ϵ x 1 1 x d x = ( 1 x ) ln ( 1 x ) + x x \implies I(x) = \dfrac{-1}{x}(\ln(\dfrac{1}{1 - x}) - x))|_{\epsilon}^{x} + \int_{\epsilon}^{x} \dfrac{1}{1 - x} dx = \dfrac{(1 - x)\ln(1 - x) + x}{x} , where lim ϵ 0 ( 1 ϵ ) ln ( 1 ϵ ) + ϵ ϵ = 0 \lim_{\epsilon \rightarrow 0} \dfrac{(1 - \epsilon)\ln(1 - \epsilon) + \epsilon}{\epsilon} = 0

w ( x ) = ϵ x 1 x 2 ( ln ( 1 1 x ) x ) 1 2 d x = ( 1 x ) ln ( 1 x ) + x x x 2 \therefore \boxed{w(x) = \int_{\epsilon}^{x} \dfrac{1}{x^2}(\ln(\dfrac{1}{1 - x}) - x) - \dfrac{1}{2} \:\ dx = \dfrac{(1 - x)\ln(1 - x) + x}{x} - \dfrac{x}{2}} on x 1 |x| \leq 1 .

Let g ( x ) = n = 3 x n 2 ( n 2 ) ( n 1 ) n d d x ( g ( x ) ) = n = 3 x n 3 ( n 1 ) n = 1 x 2 n = 3 x n 1 ( n 1 ) n g(x) = \sum_{n = 3}^{\infty} \dfrac{x^{n - 2}}{(n - 2)(n - 1)n} \implies \dfrac{d}{dx}(g(x)) = \sum_{n = 3}^{\infty} \dfrac{x^{n - 3}}{(n - 1)n} = \dfrac{1}{x^2}\sum_{n = 3}^{\infty} \dfrac{x^{n - 1}}{(n - 1)n} = ( 1 x ) ln ( 1 x ) + x x 3 1 2 x \dfrac{(1 - x)\ln(1 - x) + x}{x^3} - \dfrac{1}{2x} .

Let I ( x ) = ( 1 x ) ln ( 1 x ) + x x 3 d x I^{*}(x) = \int \dfrac{(1 - x)\ln(1 - x) + x}{x^3} \:\ dx .

Let u = ( 1 x ) ln ( 1 x ) + x , d u = ln ( 1 x ) , d v = x 3 u = (1 - x)\ln(1 - x) + x, du = -\ln(1 - x), dv = x^{-3} and v = 1 2 x 2 v = \dfrac{-1}{2x^2} \implies

I ( x ) = 1 2 x 2 ( ( 1 x ) ln ( 1 x ) + x ) 1 2 ln ( 1 x ) x 2 I(x) = \dfrac{-1}{2x^2}((1 - x)\ln(1 - x) + x) - \dfrac{1}{2}\int \dfrac{\ln(1 - x)}{x^2} .

Let u = ln ( 1 x ) , d u = 1 1 x , d v = x 2 u = \ln(1 - x), du = \dfrac{-1}{1 - x}, dv = x^{-2} and v = 1 x v = \dfrac{-1}{x} \implies

ln ( 1 x ) x 2 d x = 1 x ln ( 1 x ) 1 x + 1 1 x d x \int \dfrac{\ln(1 - x)}{x^2} dx = \dfrac{-1}{x}\ln(1 - x) - \int \dfrac{1}{x} + \dfrac{1}{1 - x} dx \implies

I ( x ) = 1 2 ( 1 x x ln ( 1 x ) + ln ( x ) ) I^{*}(x) = \dfrac{1}{2}(\dfrac{1 - x}{x}\ln(1 - x) + \ln(x)) \implies g ( x ) = 1 2 x 2 ( ( 1 x ) ln ( 1 x ) + x ) + 1 2 ( ( 1 x x ) ln ( 1 x ) + ln ( x ) ) 1 2 ln ( x ) ϵ x = g(x) = \dfrac{-1}{2x^2}((1 - x)\ln(1 - x) + x) + \dfrac{1}{2}((\dfrac{1 - x}{x})\ln(1 - x) + \ln(x)) - \dfrac{1}{2}\ln(x)|_{\epsilon}^{x} = ( ( x 1 ) 2 ln ( 1 x ) + x 2 x 2 ) ϵ x = ( x 1 ) 2 ln ( 1 x ) + x 2 x 2 3 4 = -(\dfrac{(x - 1)^2\ln(1 - x) + x}{2x^2})|_{\epsilon}^{x} = -\dfrac{(x - 1)^2\ln(1 - x) + x}{2x^2} - \dfrac{3}{4} = 2 ( x 1 ) 2 ln ( 1 x ) 2 x + 3 x 2 4 x 2 \dfrac{-2(x - 1)^2\ln(1 - x) - 2x + 3x^2}{4x^2} , where 1 2 lim ϵ 0 ( ϵ 1 ) 2 ln ( 1 ϵ ) + ϵ ϵ 2 = 3 4 \dfrac{-1}{2}\lim_{\epsilon \rightarrow 0} \dfrac{(\epsilon - 1)^2\ln(1 - \epsilon) + \epsilon}{\epsilon^2} = \dfrac{-3}{4} and x 1 |x| \leq 1

f ( x ) = n = 3 ( 1 ) n + 1 x n 2 ( n 2 ) ( n 1 ) n = \implies f(x) = \sum_{n = 3}^{\infty} (-1)^{n + 1} \dfrac{x^{n - 2}}{(n - 2)(n - 1)n} = n = 3 ( x ) n 2 ( n 2 ) ( n 1 ) n = 2 ( x + 1 ) 2 ln ( x + 1 ) 2 x 3 x 2 4 x 2 -\sum_{n = 3}^{\infty} \dfrac{(-x)^{n - 2}}{(n - 2)(n - 1)n} = \dfrac{2(x + 1)^2\ln(x + 1) - 2x - 3x^2}{4x^2} on x 1 |x| \leq 1 .

d d x ( f ( x ) ) = 1 2 ( x 2 + 2 x 2 ( x + 1 ) ln ( x + 1 ) x 3 ) \dfrac{d}{dx}(f(x)) = \dfrac{1}{2}(\dfrac{x^2 + 2x - 2(x + 1)\ln(x + 1)}{x^3})

and,

d d x ( g ( x ) ) = 1 2 ( x 2 2 x + 2 ( x + 1 ) ln ( 1 x ) x 3 ) \dfrac{d}{dx}(g(x)) = \dfrac{-1}{2}(\dfrac{x^2 - 2x + 2(x + 1)\ln(1 - x)}{x^3})

d d x ( f ( x ) ) x = a = 1 2 ( a 2 + 2 a 2 ( a + 1 ) ln ( 1 + a ) a 3 ) = \implies \dfrac{d}{dx}(f(x))|_{x = a} = \dfrac{1}{2}(\dfrac{a^2 + 2a - 2(a + 1)\ln(1 + a)}{a^3}) = d d x ( g ( x ) ) x = a \dfrac{d}{dx}(g(x))|_{x = -a}

A C \implies \overleftrightarrow{AC} is tangent to f ( x ) f(x) at A : ( 2 ( a + 1 ) 2 ln ( a + 1 ) 2 a 3 a 2 4 a 2 ) A: (\dfrac{2(a + 1)^2\ln(a + 1) - 2a - 3a^2}{4a^2}) and B D \overleftrightarrow{BD} is tangent to g ( x ) g(x) at B : ( a , 2 ( a + 1 ) 2 ln ( a + 1 ) + 2 a + 3 a 2 4 a 2 ) B:( -a, \dfrac{-2(a + 1)^2\ln(a + 1) + 2a + 3a^2}{4a^2} )

Letting a = 1 A : ( 1 , 8 ln ( 2 ) 5 4 ) a = 1 \implies A: (1, \dfrac{8\ln(2) - 5}{4}) and B : ( 1 , 5 8 ln ( 2 ) 4 ) B: (-1, \dfrac{5 - 8\ln(2)}{4}) \implies y = 1 2 ( 3 4 ln ( 2 ) ) x + 16 ln ( 2 ) 11 4 y = \dfrac{1}{2}(3 -4\ln(2))x + \dfrac{16\ln(2) - 11}{4} and y = 1 2 ( 3 4 ln ( 2 ) ) x 16 ln ( 2 ) 11 4 y = \dfrac{1}{2}(3 -4\ln(2))x - \dfrac{16\ln(2) - 11}{4} .

Using B : ( 1 , 5 8 ln ( 2 ) 4 ) m = 2 3 4 ln ( 2 ) B: (-1, \dfrac{5 - 8\ln(2)}{4}) \implies m_{\perp} = \dfrac{-2}{3 - 4\ln(2)} \implies the normal line to g ( x ) g(x) at x = 1 x = -1 is y = 2 3 4 ln ( 2 ) x + 32 ( ln ( 2 ) ) 2 44 ln ( 2 ) + 7 4 ( 3 4 ln ( 2 ) y = \dfrac{-2}{3 - 4\ln(2)}x + \dfrac{32(\ln(2))^2 - 44\ln(2) + 7}{4(3 - 4\ln(2)} .

To find point C : ( x 0 , y 0 ) C: (x_{0},y_{0}) we solve the system:

4 y 2 ( 3 4 ln ( 2 ) ) x = 16 ln ( 2 ) 11 4y - 2(3 - 4\ln(2))x = 16\ln(2) - 11

4 ( 3 4 ln ( 2 ) ) y + 8 x = 32 ( ln ( 2 ) ) 2 44 ln ( 2 ) + 7 4(3 - 4\ln(2))y + 8x = 32(\ln(2))^2 - 44\ln(2) + 7

Solving the system above we obtain:

x 0 = 4 ( 12 ( ln ( 2 ) ) 2 17 ln ( 2 ) + 5 ) 16 ( ln ( 2 ) ) 2 24 ln ( 2 ) + 13 x_{0} = \dfrac{4(12(\ln(2))^2 - 17\ln(2) + 5)}{16(\ln(2))^2 -24\ln(2) + 13}

and

y 0 = 128 ( ln ( 2 ) ) 3 + 272 ( ln ( 2 ) ) 2 96 ln ( 2 ) 23 4 ( 16 ( ln ( 2 ) ) 2 24 ln ( 2 ) + 13 ) y_{0} = \dfrac{-128(\ln(2))^3 + 272(\ln(2))^2 - 96\ln(2) - 23}{4(16(\ln(2))^2 -24\ln(2) + 13)}

Using C : ( x 0 , y 0 ) C: (x_{0}, y_{0}) and B : ( 1 , 5 8 ln ( 2 ) 4 ) x = 64 ( ln ( 2 ) ) 2 92 ln ( 2 ) + 33 16 ( ln ( 2 ) ) 2 24 ln ( 2 ) + 13 B: (-1, \dfrac{5 - 8\ln(2)}{4}) \implies \triangle{x} = \dfrac{64(\ln(2))^2 - 92\ln(2) + 33}{16(\ln(2))^2 - 24\ln(2) + 13} and y = 32 ln ( 2 ) 22 16 ( ln ( 2 ) ) 2 24 ln ( 2 ) + 13 \triangle{y} = \dfrac{32\ln(2) - 22}{16(\ln(2))^2 - 24\ln(2) + 13}

B C = 16 ln ( 2 ) 11 16 ( ln ( 2 ) ) 2 24 ln ( 2 ) + 13 0.044888 \implies BC = \dfrac{16\ln(2) - 11}{\sqrt{16(\ln(2))^2 - 24\ln(2) + 13}} \approx \boxed{0.044888} .

Bonus:

Let ( 0 < a 1 ) (0 < a \leq 1) and j j be a odd positive integer and x 1 |x| \leq 1 .

Let w ( x ) = n = j + 2 x n j ( n j ) ( n j + 1 ) ( n ) w(x) = \sum_{n = j + 2}^{\infty} \dfrac{x^{n - j}}{(n - j)(n - j + 1) \cdot \cdot \cdot (n)}

g ( x ) = n = j + 2 x n j 1 ( n j 1 ) ( n j ) ( n ) g(x) = \sum_{n = j + 2}^{\infty} \dfrac{x^{n - j - 1}}{(n - j - 1)(n - j) \cdot \cdot \cdot (n)} \implies
d d x ( g ( x ) ) = n = j + 2 x n j 2 ( n j ) ( n ) = \dfrac{d}{dx}(g(x)) = \sum_{n = j + 2}^{\infty} \dfrac{x^{n - j - 2}}{(n - j) \cdot \cdot \cdot (n)} = 1 x 2 n = j + 1 x n j ( n j ) ( n j + 1 ) ( n ) = 1 x 2 w ( x ) \dfrac{1}{x^2} \sum_{n = j + 1}^{\infty} \dfrac{x^{n - j}}{(n - j)(n - j + 1) \cdot \cdot \cdot (n)} = \dfrac{1}{x^2} w(x)

g ( x ) = lim ϵ 0 ϵ x 1 x 2 w ( x ) \implies g(x) = \lim_{\epsilon \rightarrow 0}\int_{\epsilon}^{x} \dfrac{1}{x^2} w(x) .

f ( x ) = n = j + 2 ( 1 ) n + 1 x n j 1 ( n j 1 ) ( n j ) ( n ) = f(x) = \sum_{n = j + 2}^{\infty} (-1)^{n + 1} \dfrac{x^{n - j - 1}}{(n - j - 1)(n - j) \cdot \cdot \cdot (n)} = n = j + 2 ( x ) n j 1 ( n j 1 ) ( n j ) ( n ) = -\sum_{n = j + 2}^{\infty} \dfrac{(-x)^{n - j - 1}}{(n - j - 1)(n - j) \cdot \cdot \cdot (n)} = g ( x ) f ( a ) = g ( a ) -g(-x) \implies \boxed{f(a) = -g(-a)}

d d x ( f ( x ) ) x = a = n = j + 2 ( 1 ) n + 1 a n j 2 ( n j ) ( n j + 1 ) ( n ) = \dfrac{d}{dx}(f(x))|_{x = a} = \sum_{n = j + 2}^{\infty} (-1)^{n + 1} \dfrac{a^{n - j - 2}}{(n - j)(n - j + 1) \cdot \cdot \cdot (n)} = 1 a 2 n = j + 2 ( 1 ) n + 1 a n j ( n j ) ( n j + 1 ) ( n ) = \dfrac{1}{a^2} \sum_{n = j + 2}^{\infty} (-1)^{n + 1} \dfrac{a^{n - j}}{(n - j)(n - j + 1) \cdot \cdot \cdot (n)} = 1 a 2 n = j + 2 ( a ) n j ( n j ) ( n j + 1 ) ( n ) = \dfrac{1}{a^2} \sum_{n = j + 2}^{\infty} \dfrac{(-a)^{n - j}}{(n - j)(n - j + 1) \cdot \cdot \cdot (n)} = 1 a 2 w ( a ) = d d x ( g ( x ) ) x = a \dfrac{1}{a^2} w(-a) = \dfrac{d}{dx}(g(x))|_{x = -a}

d d x ( f ( x ) ) x = a = d d x ( g ( x ) ) x = a \therefore \boxed{\dfrac{d}{dx}(f(x))|_{x = a} = \dfrac{d}{dx}(g(x))|_{x = -a}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...